Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/adma.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Molybdenum Carbide–Graphene Composites for 3D Foldable Paper Electronics

Abstract: Versatile and low-cost manufacturing processes/materials are essential for the development of paper electronics. Here, a direct-write laser patterning process is developed to make conductive molybdenum carbide-graphene (MCG) composites directly on paper substrates. The hierarchically porous MCG structures are converted from fibrous paper soaked with the gelatin-mediated inks containing molybdenum ions. The resulting Mo C and graphene composites are mechanically stable and electrochemically active for various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
170
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 27 publications
1
170
0
Order By: Relevance
“…In addition, recent research reveals that transient CO 2 laser heating can convert various polymer films into porous graphene with continuous structures under ambient atmospheres . Applications of laser‐induced porous graphene in flexible supercapacitors, wearable strain sensors, and artificial throat have been recently demonstrated . In this Communication, we report a general strategy of using porous materials to make multifunctional on‐skin electronics with high gas permeability.…”
mentioning
confidence: 94%
“…In addition, recent research reveals that transient CO 2 laser heating can convert various polymer films into porous graphene with continuous structures under ambient atmospheres . Applications of laser‐induced porous graphene in flexible supercapacitors, wearable strain sensors, and artificial throat have been recently demonstrated . In this Communication, we report a general strategy of using porous materials to make multifunctional on‐skin electronics with high gas permeability.…”
mentioning
confidence: 94%
“…[28] The transparency of a logo pattern induced on the PI film and then transferred to the WPU substrate is shown in Figure 1b, which also indicates the convenience and universality of our stretchable MSC fabrication method. [40,41] More importantly, the high-magnification image in Figure 1e reveals that LIG is decorated evenly with small round convex particles, indicating a portion of the hybrid NiO/Co 3 O 4 nanoparticles were distributed on surface. [12,15] While in situ synthesized NiO/Co 3 O 4 /LIG shows a completely different morphology (Figure 1d) in that the entire structure is composed of multilayer graphene, which is a synergistic result of the simultaneous carbonization of PI and gelatin.…”
Section: Morphology and Structure Analysismentioning
confidence: 96%
“…[37] Second, stretchable MSCs assembled on PDMS and silicone rubber, which cannot be degraded under natural conditions, pose a potential threat to the living environment. [40][41][42] It was found that the gelatin could modify the surface morphology and wettability of NiO/ Co 3 O 4 /LIG. [39] In this work, a gelatin-mediated ink containing Ni and Co ions was coated onto a PI film and subjected to laser direct writing, during which the gelatin was completely cocarbonized with PI while in situ synthesizing laser-induced graphene/NiO/ Co 3 O 4 (NiO/Co 3 O 4 /LIG).…”
mentioning
confidence: 99%
“…Among these materials, 2D TMCs possess excellent electrical conductivity, electrochemical activity, high surface area, and strong chemical resilience . These make them particularly desirable for various clean energy applications such as energy storage and catalysis . The most widely applied method toward 2D TMCs requires a selective etching process from their ternary MAX phases (M n +1 AX n , M is transition metal, A is a group 12–16 elements, and X is C or N) using fluoride‐based etching solutions to selectively remove the element “A” from a MAX crystal .…”
Section: Summary Of Catalyst Activity Of Different Carbides For Her Imentioning
confidence: 99%